(untitled) (Research, Society and Development, 2020)
Anxiety disorder is one of the most prevalent neuropsychiatric conditions with about 264 million people worldwide living with this disorder. It is triggered when an individual faced with a given situation or event is unable to respond to the demands and feels a threat to their existence or essential values. This disorder has a multifactorial nature in its etiology, emphasizing mainly genetic, environmental and neurobiological factors. The main medication agents most used are benzodiazepines and non-benzodiazepines, however the use and recommendation of these agents is limited. This study is classified in a qualitative narrative review. In addition, the drug treatment of symptoms completely remains unknown. Thus, this review aims to discuss the main physiological bases of this disorder, as well as the treatment and its effects.